STRATEGI PEMBELAJARAN DALAM MENINGKATKAN PENDIDIKAN KARAKTER SISWA PADA KEGIATAN EKSTRAKURIKULER TARI DI SDN 065012 - Edi Putra Wijaya Manalu; Anton Sitepu; Ester Julinda Simarmata; Reflina Sinaga; Paska Sriulina Tarigan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is an important part in shaping attitudes and behavior, students in elementary schools, This study aims to determine the learning strategies used by teachers in improving students' character education through dance extracurricular activities at SDN 065012. The study used a qualitative approach with data collection in the form of observation, interviews, and documentation. The results of the study showed that teachers implemented habituation strategies, role models, providing motivation in groups, and repeating exercises. These strategies were able to improve the character of discipline, responsibility in groups, compliance with rules, and students' self-confidence. The obstacles faced included, lack of discipline among students, differences in abilities, limited facilities and infrastructure, and lack of parental support. Efforts made by teachers were to provide mentoring, motivation, evaluation, and establish communication with parents. Thus, extracurricular activities, dance, have a positive message in improving students' character education at SDN 065012.